Epidemiology and control of human schistosomiasis in Tanzania - Mazigo, Humphrey D (BioMed Central, 2012)
In Tanzania, the first cases of schistosomiasis were reported in the early 19th century. Since then, various studies have reported prevalences of up to 100% in some areas. However, for many years, there have been no sustainable control programmes and systematic data from observational and control studies are very limited in the public domain. To cover that gap, the present article reviews the epidemiology, malacology, morbidity, and the milestones the country has made in efforts to control schistosomiasis and discusses future control approaches. The available evidence indicates that, both urinary and intestinal schistosomiasis are still highly endemic in Tanzania and cause significant morbidity.Mass drug administration using praziquantel, currently used as a key intervention measure, has not been successful in decreasing prevalence of infection. There is therefore an urgent need to revise the current approach for the successful control of the disease. Clearly, these need to be integrated control measures.